2014
DOI: 10.1161/hypertensionaha.114.03188
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Angiotensin II Type 2 Receptors in the Solitary–Vagal Complex Blunts Renovascular Hypertension

Abstract: Angiotensin II increases and decreases arterial pressure by acting at angiotensin type 1 and type 2 receptors respectively. Renovascular hypertensive rats exhibit a high level of activity of the peripheral and central renin-angiotensin system. Therefore, in the present study we evaluated the effect of increasing the expression of angiotensin type 2 receptors in the solitary-vagal complex [nucleus of the solitary tract/dorsal motor nucleus of the vagus], a key brainstem region for cardiovascular regulation, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
5
32
1
1
Order By: Relevance
“…Our observation that C21 mediated stimulation of central AT 2 R prevented the spontaneous blood pressure increase in SHR is in line with the recent demonstration by Blanch et al that increased expression of AT 2 R in the solitary-vagal complex, a brainstem region important in the control of blood pressure, attenuates the increase in arterial pressure observed in a rat model with 2-kidney 1-clip renovascular hypertension [32]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observation that C21 mediated stimulation of central AT 2 R prevented the spontaneous blood pressure increase in SHR is in line with the recent demonstration by Blanch et al that increased expression of AT 2 R in the solitary-vagal complex, a brainstem region important in the control of blood pressure, attenuates the increase in arterial pressure observed in a rat model with 2-kidney 1-clip renovascular hypertension [32]. …”
Section: Discussionsupporting
confidence: 92%
“…It is tempting to speculate that the prevention of the progression of hypertension in SHR induced by central AT 2 R stimulation observed in the present study is, in part, related to this restoration of baroreceptor function. These results also confirm the recent observation that increased expression of AT 2 R in the solitary-vagal complex restores baroreflex function and sympathetic modulation of arterial pressure to normal values in rats with 2-kidney 1-clip renovascular hypertension, another rat model characterized by baroreceptor impairment and increased sympathetic tone [32]. …”
Section: Discussionsupporting
confidence: 90%
“…Brain AT 1 receptors have been implicated in the regulation of blood pressure35, while brain AT 2 receptors seem to modulate the inhibition of the sympathetic nervous system36. Actually, increasing central AT 2 receptor expression attenuated the development of renovascular hypertension in the rat37. In the present study, we characterized which subtype (AT 1 or AT 2 ) in the brain is involved in the i.c.v.…”
Section: Discussionmentioning
confidence: 84%
“…Electrophysiological studies examining the CNS cardiovascular control centres of AT1Ra knockout mice suggest that AT2R in the RVLM play an antagonistic role against AT1R-mediated actions of Ang II within this nucleus [34]. Furthermore, virally-mediated over expression of AT2R within the RVLM [35] or NTS [36] elicits respective decreases in mean arterial blood pressure of normotensive rats and in 2 kidney-1 clip hypertensive rats. In the latter study, it was also demonstrated that AT2R over expression in the NTS restores baroreflex sensitivity [36].…”
Section: Central Nervous System Effects Of At2r Stimulation On Blood mentioning
confidence: 99%
“…Furthermore, virally-mediated over expression of AT2R within the RVLM [35] or NTS [36] elicits respective decreases in mean arterial blood pressure of normotensive rats and in 2 kidney-1 clip hypertensive rats. In the latter study, it was also demonstrated that AT2R over expression in the NTS restores baroreflex sensitivity [36]. The recent availability of C21, has enabled Gao et al to demonstrate that infusion of this agent into the cerebroventricles lowers blood pressure in normotensive rats [37,38], and more recently to show that similar infusions into rats with heart failure suppresses sympathetic outflow by improving baroreflex sensitivity [39].…”
Section: Central Nervous System Effects Of At2r Stimulation On Blood mentioning
confidence: 99%